RELEVANSI KEHARAMAN BERTATO DENGAN LARANGAN DONOR DARAH BAGI ORANG BERTATO - Nasution, Muhammad Arsad; Siregar , Rosnani; Baharuddin, Didin (IAIN Ambon, 2024)
Tattooing is a part of art that many people do. However, Islamic law prohibits people with tattoos, on the other hand, medical science also prohibits people with tattoos from donating blood. This article tries to explain whether there is a match (relevance) between the prohibition of tattooing according to Islamic law and the prohibition of blood donation for people with tattoos according to medical science. To answer this question, the author collects data from various sources of scientific writings in the form of books or journals that describe the prohibition of tattooing according to Islamic law and also scientific writings related to the prohibition of blood donation for people with tattoos according to health. This disclosure is important to explore to uncover the maqasid al-syari' in prohibiting the act of tattooing according to Islamic law. The results obtained from the scientific data above show that the Prophet Muhammad forbade his people from getting tattoos. This prohibition is stated in several hadiths of the Prophet Muhammad with a clear prohibition expression, namely using the phrase